The Influence of Environmental Sanitation and Community Behavior on Dengue Fever Incidence: A Case-Control Study in Siantar Utara District - Deli Syaputri; Samuel Marganda (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Dengue remains a persistent urban health challenge in Indonesia. Household-level factors, such as physical barriers and daily behaviours, may influence indoor vector-host contact but are inconsistently addressed in routine control programs. We conducted a community-based case-control study in Siantar Utara (Pematang Siantar, North Sumatra) to assess household attributes associated with dengue occurrence. Cases were physician-confirmed dengue patients; controls were neighbourhood peers without recent dengue-compatible illness. A total of 36 case and 36 control households were enrolled. Prespecified exposures included: window/ventilation screening (≥50% of openings with intact mesh), presence of larvae in water-holding containers (WSC) and non-WSC, indoor hanging clothes (≥5 garments visible), and health-officer support within the preceding 3 months. Data were collected through standardized interviews and on-site observations. Associations were analyzed using χ² and Fisher's exact tests (α = 0.05). Households lacking mesh screening were disproportionately represented among cases, with a statistically significant association between screening and dengue status (p = 0.011). Indoor hanging clothes were more common in case households and significantly associated with dengue incidence (p = 0.016). Health-officer support demonstrated a strong protective effect (p < 0.001). Larval presence in WSC and non-WSC was not statistically significant (p = 0.326 and p = 0.233, respectively These findings support a mechanistic pathway in which intact screening and reduced indoor resting sites lower exposure to day-biting Aedes aegypti. In this urban Indonesian context, window/ventilation screening and clothing-storage practices were associated with dengue occurrence, highlighting modifiable, low-cost targets for the 3M Plus strategy. Programmatic integration should prioritize mesh coverage and integrity checks, counseling to reduce indoor hanging garments, routine container management, and regular cadre visits, with monitoring via ABJ and simple household indicators. Further cluster or stepped-wedge trials are recommended to validate effectiveness and sustainability. Keyword: Dengue, Aedes aegypti, Environmental, Sanitation